2009
DOI: 10.1186/1471-230x-9-61
|View full text |Cite
|
Sign up to set email alerts
|

Small intestinal bacterial overgrowth mimicking acute flare as a pitfall in patients with Crohn's Disease

Abstract: BackgroundSmall intestinal bacterial overgrowth (SIBO) is characterized by excessive proliferation of colonic bacterial species in the small bowel. Potential causes of SIBO include fistulae, strictures or motility disturbances. Hence, patients with Crohn's Disease (CD) are especially predisposed to develop SIBO. As result, CD patients may experience malabsorption and report symptoms such as weight loss, watery diarrhea, meteorism, flatulence and abdominal pain, mimicking acute flare in these patients.MethodsOn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
56
1
6

Year Published

2010
2010
2021
2021

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(68 citation statements)
references
References 14 publications
5
56
1
6
Order By: Relevance
“…One, the ileo-cecal valve serves as an important barrier between the ileum and cecum that not only regulates flow of contents from the small bowel to the cecum but also prevents reflux of contents and transmigration of colonic contents and bacteria into the small bowel. Loss of ileocecal valve is a known risk factor for the development of SIBO [10,11]. And second is that subtotal colectomy alters the natural anatomy together with postoperative changes such as adhesions may lead to altered gut motility resulting in increased risk of SIBO.…”
Section: Discussionmentioning
confidence: 99%
“…One, the ileo-cecal valve serves as an important barrier between the ileum and cecum that not only regulates flow of contents from the small bowel to the cecum but also prevents reflux of contents and transmigration of colonic contents and bacteria into the small bowel. Loss of ileocecal valve is a known risk factor for the development of SIBO [10,11]. And second is that subtotal colectomy alters the natural anatomy together with postoperative changes such as adhesions may lead to altered gut motility resulting in increased risk of SIBO.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, patients with CD are especially predisposed to develop SIBO. 57 Rana et al have pointed out that the occurrence of SIBO was significantly higher in CD patients (45.2%) as compared to controls (0.86%) and UC patients (17.8%). 58 Also Castiglione et al, in their study, have found a higher percentage of SIBO in CD patients.…”
Section: Extension Of the Diseasementioning
confidence: 94%
“…In their studies Klaus et al and Castiglione et al have shown that the prevalence of SIBO is higher in patients with prior ileocecal resection than in those who have not undergone prior surgery or multiple respective procedures. 57,59 One reason might be a change, especially a reduction in motility in the bowel following surgery. This may be reflected in data reported by Castiglione et al, who found a prolongation of oro-cecal transit time in patients with CD compared to healthy controls.…”
Section: Extension Of the Diseasementioning
confidence: 99%
See 1 more Smart Citation
“…Likewise, stricture formation with chronic dilatation is usually associated with overgrowth. This may be seen in Crohn's disease, radiation enteritis, or children with congenital anomalies such as intestinal atresia who have postoperative strictures with some degree of dysmotility [30,31].…”
Section: Prevalence and Associated Conditionsmentioning
confidence: 97%